Nutritional Literacy, Knowledge and Compliance with a Simple Low-Carbohydrate Diet in Type 2 Diabetes Mellitus - Jesika; Simbolon, Demsa (Futurity Medicine, 2026)
Diabetes Mellitus (DM) Type 2 (DMT2) is a condition that can be caused by a lack of insulin resistance and is associated with a general lack of insulin resistance, as the highest cause of pain and death in the non-communicable disease group. Aims: This study aims to determine the effects of a simple kairbohydrate soaking diet before it is given nutritional literacy through the medial Booklet of the intervention group in the control group of patients with DMT2. Methodology: This type of research is based on a Quaisi Experiment with a Two Group Pre-Test Post-Test design that is carried out in Kota Bengkulu. According to this research, 66 patients with DMT2 were assisted at the Pasar Ikan Health Center. The study is expected to be conducted in April-May 2024. The following tests were used, namely the Chi-Squaire test, the Mainn-Whitney U Test, the Independent T-Test, the Paiired T-Test, and the Wilcoxon Signed U Test. Results: Participants were randomised to the intervention group with a p-vailue 0.0001<0.05, nutritional literacy with a mediated Booklet. Likewise aided the control group with p-vailue gain 0.001<0.05 nutritional literacy with Leaiflet-mediated nutrients. The Booklet-mediated intervention group was also aided by the intervention group with a p-value gain 0.0001<0.05, in nutritional literacy with Booklet-mediated nutrients. Likewise helped the control group with a p-vailue gain of 0.0001<0.05 nutritional literacy with Leaiflet-mediated gain. Scientific Novelty: The novelty of this research lies in Focus on nutrition literacy interventions that are specifically aimed at improving adherence to a detailed type of diet, i.e. a low-carbohydrate diet, which is rarely the sole focus in nutrition literacy studies for people with DMT2. Conclusion: There is an effect of adherence to a simple low-carbohydrate diet on DMT2 before and after being Granted Nutrition Literacy Activities.